68Ga-DOTATATE Uptake in Solitary Pancreatic Metastasis From Clear Cell Renal Cancer. (September 2017) - Vamadevan, Shankar; Le, Ken; Shen, Lily; Loh, Han; Mansberg, Robert
Abstract : Abstract: A 64-year-old man with a lesion of the pancreatic tail was referred for 68 Ga-DOTATATE PET/CT imaging. His medical history included previous metastatic clear cell renal cell cancer. 68 Ga-DOTATATE PET/CT demonstrated increased DOTATATE uptake (SUVmax 10.5) in a pancreatic tail lesion. Histopathology of the resected lesion confirmed clear renal cell cancer metastasis. This case illustrates that clear cell renal cancer metastasis can demonstrate 68 Ga-DOTATATE accumulation.